2021
DOI: 10.1080/16549716.2021.1930655
|View full text |Cite
|
Sign up to set email alerts
|

Migrant health penalty: evidence of higher mortality risk among internal migrants in sub-Saharan Africa

Abstract: d'analyse du changement dans l'histoire et les sociétés contemporaines (IACCHOS),

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 42 publications
1
10
0
Order By: Relevance
“…Although non-communicable disease (NCD) mortality is strongly associated with low socio-economic conditions 17 and largely preventable through timely access to healthcare, previous studies found no consistent differences in all-cause and NCD mortality between internal migrants and non-migrants in LMICs. 18 , 19 , 20 , 21 , 22 , 23 Notably, the studies conducted in Latin America found evidence of lower all-cause mortality among internal and international migrants compared to local-born non-migrants in Peru 20 and Brazil, 23 respectively. In contrast to LMICs, several studies have reported mortality advantages among international migrants living in HICs.…”
Section: Discussionmentioning
confidence: 99%
“…Although non-communicable disease (NCD) mortality is strongly associated with low socio-economic conditions 17 and largely preventable through timely access to healthcare, previous studies found no consistent differences in all-cause and NCD mortality between internal migrants and non-migrants in LMICs. 18 , 19 , 20 , 21 , 22 , 23 Notably, the studies conducted in Latin America found evidence of lower all-cause mortality among internal and international migrants compared to local-born non-migrants in Peru 20 and Brazil, 23 respectively. In contrast to LMICs, several studies have reported mortality advantages among international migrants living in HICs.…”
Section: Discussionmentioning
confidence: 99%
“…This provides evidence for the migrant health penalty, which posits that individuals who migrate experience intrinsic risks that heighten their risk for poor HIV outcomes. 16 Mobile populations may face structural barriers to care that lead to treatment interruptions, 17 which increases risk of viremia and other poor treatment outcomes. 26,27 In Namibia, high viremia rates were found along transport corridors, signifying that high rates of viremia among migrants may also correspond to high community-level viremia.…”
Section: Discussionmentioning
confidence: 99%
“…[13][14][15] Similarly, estimates of population-level rates of viremia among persons living with HIV may be biased by the exclusion of new households, and most evidence in SSA suggests worse HIV outcomes for migrants compared to non-migrants due to gaps in the continuity of care. [16][17][18] Here, we explored how systematic exclusion of in-migrants in new structures may bias survey samples and alter HIV estimates. We first described characteristics of migrant individuals in new household structures, comparing them to both migrants and non-migrants in existing household structures.…”
Section: Exclusion Of New Households From Open Population-based Cohor...mentioning
confidence: 99%
See 1 more Smart Citation
“…Research exploring health amongst African migrants is limited, particularly with younger populations [ 39 ]. Even less work has focused on possibilities for health promotion with young migrant groups—particularly in Africa, including detailed exploration of the ways young migrants engage with (or not) health-enhancing practices.…”
Section: Discussionmentioning
confidence: 99%